Too Big To Handle? Interdisciplinary Perspectives on the Question of Why Societies Ignore Looming Disasters. (May 2016) - van Aaken, Anne; Antonovics, Janis
Abstract : There has to be a detailed and in‐depth analysis of why we don't solve looming disasters.